Epigenetic Mechanisms Involved in Cisplatin-Induced Nephrotoxicity: An Update - Pía Loren; Nicolás Saavedra; Kathleen Saavedra; Tomás Zambrano; Patricia Moriel; Luis A. Salazar (MDPI AG, 2021)
Cisplatin is an antineoplastic drug used for the treatment of many solid tumors. Among its various side effects, nephrotoxicity is the most detrimental. In recent years, epigenetic regulation has emerged as a modulatory mechanism of cisplatin-induced nephrotoxicity, involving non-coding RNAs, DNA methylation and histone modifications. These epigenetic marks alter different signaling pathways leading to damage and cell death. In this review, we describe how different epigenetic modifications alter different pathways leading to cell death by apoptosis, autophagy, necroptosis, among others. The study of epigenetic regulation is still under development, and much research remains to fully determine the epigenetic mechanisms underlying cell death, which will allow leading new strategies for the diagnosis and therapy of this disease.